Kinematics Analysis of a Parallel Mixing Machine and Its Scale Optimal Design - Chen Jing; Guo Qian; Zhu Wei (Jixie chuandong)
A single input and multi-dimensional output 2RRS-S parallel mechanism was proposed based on the position and orientation characteristics (POC), and its topological structure, degree of freedom, and coupling degree were analyzed. A forward motion solution model of the mechanism was established by using the topological feature motion modeling method based on the coupling degree and verified through simulation models. According to the material mixing requirements, a three-dimensional model of a multi-dimensional mixing machine based on the 2RRS-S parallel mechanism was designed, and its motion trajectory and motion characteristics of attitude angles were simulated. Taking the variation change of the attitude angles of the moving platform as the objective function, the differential evolution algorithm was used to optimize the scale parameters of the mechanism, and the obtained mechanism has better mixing motion performance than that before the optimization.